EDUKASI AKUNTANSI BAGI SISWA NON AKUNTANSI SEBAGAI SALAH SATU PERSIAPAN KURIKULUM MERDEKA - Lucia Ari Diyani; Chita Oktapriana (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
The Minister of Education and Culture of the Republic of Indonesia 2020 launched MBKM Program. The goal of MBKM is for someone to have the opportunity to study outside their study program so that they have other competencies outside the core competencies in their study program. The MBKM program gave rise to the idea of ​​accounting training for non-accounting students. The implementation of service with this service-learning method has achieved its goal; namely, the level of student understanding has increased, and the level of knowledge and insight has also increased. Eighty-three non-accounting students attended this training. The increase in understanding varies between 44-79% for each student, while the level of usefulness of the training, each student's answer shows the number 81-88% answered Very Useful, and the rest answered Usefully. From each question item in the satisfaction questionnaire, those who answered Very Satisfied ranged from 70-99%, and the rest answered Satisfied. While satisfaction with the implementation of the training as a whole, 90% of students answered Very satisfied, and 10% answered Satisfied. The last question concerns the following training material students are interested in; the highest number of enthusiasts, as much as 24%, chose Sharia Accounting.  ---  Program Merdeka Belajar Kampus Merdeka (MBKM) telah dicanangkan Menteri Pendidikan dan Kebudayaan Republik Indonesia pada tahun 2020. Tujuan MBKM adalah agar seseorang mendapatkan kesempatan belajar diluar program studinya sehingga memiliki kompetensi lain diluar kompetensi inti yang ada pada program studinya. Program MBKM memunculkan gagasan pelatihan akuntansi bagi siswa non jurusan akuntansi. Kurikulum MBKM telah diterapkan di perguruan tinggi, namun untuk setingkat SMA dan SMK belum diterapkan. Pelaksanaan pengabdian dengan service-learning method ini telah tercapai tujuannya yaitu tingkat pemahaman siswa meningkat, tingkat pengetahuan dan wawasan juga meningkat. Pelatihan ini diikuti 83 siswa non jurusan akuntansi. Kenaikan pemahaman bervariasi antara 44-79% pada tiap siswa, sedangkan tingkat kebermanfaatan pelatihan, jawaban tiap siswa menunjukkan angka 81-88% menjawab Sangat Bermanfaat dan sisanya menjawab Bermanfaat. Dari setiap butir pertanyaan pada angket kepuasan, yang menjawab Sangat Puas berkisar antara 70-99% dan sisanya menjawab Puas. Sedangkan Kepuasan terhadap pelaksanaan pelatihan secara keseluruhan, 90% siswa menjawab Sangat puas dan 10% menjawab Puas. Pertanyaan terakhir adalah materi pelatihan selanjutnya yang diminati siswa, jumlah peminat tertinggi sebanyak 24% memilih Akuntansi Syariah.